Sidestream Smoke Extracts from Harm-Reduction and Conventional Camel Cigarettes Inhibit Osteogenic Differentiation via Oxidative Stress and Differential Activation of intrinsic Apoptotic Pathways - Nicole R. L. Sparks; Lauren M. Walker; Steven R. Sera; Joseph V. Madrid; Michael Hanna; Edward C. Dominguez; Nicole I. zur Nieden (MDPI AG, 2022)
Epidemiological studies suggest cigarette smoking as a probable environmental factor for a variety of congenital anomalies, including low bone mass, increased fracture risk and poor skeletal health. Human and animal in vitro models have confirmed hypomineralization of differentiating cell lines with sidestream smoke being more harmful to developing cells than mainstream smoke. Furthermore, first reports are emerging to suggest a differential impact of conventional versus harm-reduction tobacco products on bone tissue as it develops in the embryo or in vitro. To gather first insight into the molecular mechanism of such differences, we assessed the effect of sidestream smoke solutions from Camel (conventional) and Camel Blue (harm-reduction) cigarettes using a human embryonic stem cell osteogenic differentiation model. Sidestream smoke from the conventional Camel cigarettes concentration-dependently inhibited in vitro calcification triggered by high levels of mitochondrially generated oxidative stress, loss of mitochondrial membrane potential, and reduced ATP production. Camel sidestream smoke also induced DNA damage and caspase 9-dependent apoptosis. Camel Blue-exposed cells, in contrast, invoked only intermediate levels of reactive oxygen species insufficient to activate caspase 3/7. Despite the absence of apoptotic gene activation, damage to the mitochondrial phenotype was still noted concomitant with activation of an anti-inflammatory gene signature and inhibited mineralization. Collectively, the presented findings in differentiating pluripotent stem cells imply that embryos may exhibit low bone mineral density if exposed to environmental smoke during development.